Novel insights about the MDM2/MDM4 heterodimer. (3rd March 2016) - Moretti, Fabiola
ABSTRACT: MDM2 (mouse double minute 2 homolog) and MDM4 (double minute 4 human homolog, also known as MDMX) inhibit the activity of tumor protein p53 (TP53, best known as p53) through their heterodimerization. New evidence indicates that under stress conditions the heterodimer is modified, leading to different activities of the single molecules. In particular, following lethal DNA damage, MDM2 and MDM4 dissociate and MDM4 promotes the stabilization of homeodomain-interacting protein kinase 2 (HIPK2) and the phosphorylation of p53, resulting in transcriptional repression of antiapoptotic targets of p53/HIPK2.